Soil N2O and CH4 emissions from fodder maize production with and without riparian buffer strips of differing vegetation - Jerry C. Dlamini; L. M. Cardenas; E. H. Tesfamariam; R. M. Dunn; J. Evans; J. M. B. Hawkins; M. S. A. Blackwell; A. L. Collins (Plant and Soil, 2022)
Purpose Nitrous oxide (N 2 O) and methane (CH 4 ) are some of the most important greenhouse gases in the atmosphere of the 21st century. Vegetated riparian buffers are primarily implemented for their water quality functions in agroecosystems. Their location in agricultural landscapes allows them to intercept and process pollutants from adjacent agricultural land. They recycle organic matter, which increases soil carbon (C), intercept nitrogen (N)-rich runoff from adjacent croplands, and are seasonally anoxic. Thus processes producing environmentally harmful gases including N 2 O and CH 4 are promoted. Against this context, the study quantified atmospheric losses between a cropland and vegetated riparian buffers that serve it. Methods Environmental variables and simultaneous N 2 O and CH 4 emissions were measured for a 6-month period in a replicated plot-scale facility comprising maize ( Zea mays L.). A static chamber was used to measure gas emissions. The cropping was served by three vegetated riparian buffers, namely: (i) grass riparian buffer; (ii) willow riparian buffer and; (iii) woodland riparian buffer, which were compared with a no-buffer control. Results The no-buffer control generated the largest cumulative N 2 O emissions of 18.9 kg ha − 1 (95% confidence interval: 0.5–63.6) whilst the maize crop upslope generated the largest cumulative CH 4 emissions (5.1 ± 0.88 kg ha − 1 ). Soil N 2 O and CH 4 -based global warming potential (GWP) were lower in the willow (1223.5 ± 362.0 and 134.7 ± 74.0 kg CO 2 -eq. ha − 1 year − 1 , respectively) and woodland (1771.3 ± 800.5 and 3.4 ± 35.9 kg CO 2 -eq. ha − 1 year − 1 , respectively) riparian buffers. Conclusions Our results suggest that in maize production and where no riparian buffer vegetation is introduced for water quality purposes (no buffer control), atmospheric CH 4 and N 2 O concerns may result.